Sequencing and Annotated of Goat's Milk using Bioinformatics Tool: ClustalX - Muhammad Najmi Mohammad Fauzi; Aisyah Aqilah Abu Bakar; Liyana Amalina Adnan; Tg Ainul Farha Tg Abdul Rahman; Nurdalila A’wani Abdul Aziz (USIM Press, 2024)
MJoSHT2021, Volume 7, Issue 1, eISSN: 2601-0003